The sex offender register: politics, policy and public opinion - Thomas, Terry (Routledge, 2021)
"The Sex Offender Register examines the origins, history, structure and legalities of the UK sex offender register, and explores how political and public opinion has influenced the direction the policy of registration has taken. Delving into the origins of the UK sex offender register and how the registration policy has evolved, this book provides an understanding of the register and its contribution to 'public protection' while attempting to see the register as a policy that has grown and developed and as having an 'organic' life of its own. The sex offender register is designed as a form of 'public protection' rather than a punishment, requiring offenders to notify the police of their circumstances and to accept a degree of 'offender management' from the police. The book: Puts the development of the Register in its political, social and ethical context Considers the position of children and young people as offenders Outlines the movement of registered offenders across international borders Analyses how offenders can be removed from the register Explores how other countries in the UK manage sex offenders through registers Asks questions about the efficacy of the register and what contribution it makes to 'public protection' Looks at specific aspects of registration including the management of information Delves into the experience of life on the register Examines the influence of public opinion Discusses the role of the police as custodians of the register and as 'offender managers' Exploring the different pressures brought to bear on the register, this book provides an authoritative starting point for Police Officers, Social Workers, Probation Officers, Magistrates, students of Criminology, Criminal Justice and Policing, and the general reader wanting to understand where the UK sex offender register originated from and how it operates today"--